Perkembangan Sosial Emosional Anak Usia Dini Melalui Permainan Papan Emoji - Amaliah Amaliah; Nurmaliana Harahap; Marlina Marlina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The social emotional development of early childhood ia an important aspect that supports the formation of their character and interaction abilities in the future. One effective way to support this development is through an interactive and fun play approach. Emoji board games are a creative medium for helping children recognize, express and manage their emotions. By using emoji symbols that are easy for children to understand, this game provides an interesting learning experience while improving children's abilities in communicating, working together and understanding other people's feelings. Apart from that, this game also helps children build self-confidence and empathy, which are important foundations in social interactions. Through a directed play process, children can develop social emotional skills optimally, so they are ready to face challenges in the family and school environment.